Sustainable technology for coconut processing: Biomass-powered dryer and performance evaluation - Prabhu, C. Naveen; Dhanushkodi, S.; Sudhakar, K. (Elsevier B.V., 2025)
Coconut kernel drying is a critical step in copra production, a vital commodity in many tropical regions, where it is used for food, oil, and other products. Traditional methods, such as sun drying, rely heavily on weather conditions, often leading to inconsistent product quality and extended drying times. Additionally, these methods can be labor-intensive and susceptible to contamination. Biomass energy has emerged as a promising alternative to conventional energy sources, particularly in rural areas with abundant agricultural residues. This study aims to develop and test a small-scale biomass dryer using sustainable biomass fuel to dry coconut kernels more efficiently, with even heat distribution and reduced drying times. The design incorporates a biomass heater, blower, and a well-designed drying chamber to optimize efficiency. The strategically designed chimney effect ensures uniform temperature distribution across the drying tray, leading to consistent and thorough drying. The experimental setup involved using a representative sample of 250 g extracted from 5 kg of coconut kernels to evaluate the dryer’s performance under controlled conditions. A notable achievement of the dryer was its consistent ability to maintain a critical temperature range of 67–75 ◦C, which is crucial for ensuring effective and efficient drying processes. Compared to traditional sun drying (22–24 h), this dryer significantly reduces drying time (9 h), achieving a final moisture content of 3.2 %. This emphasizes the drying chamber’s superior efficiency (48.16 %) for coconut kernel drying, partly attributed to its innovative design feature. The dryer utilizes biomass fuel, offering a sustainable and potentially cost-effective alternative to electric or conventional drying methods and providing reassurance about its economic viability. Its simple construction and efficient operation make it ideal for small-scale copra processing in rural and urban settings, contributing significantly to sustainability in agricultural operations.